Paper-based Stencil-free Enzymatic Sensor with Ink and Wire Electrodes. (2017) - Amor-Gutiérrez, O.; Rama, E. Costa; Costa-García, A.; Fernández-Abedul, M.T.
Abstract: Analytical Chemistry is nowadays one of the branches of Chemistry that has changed enormously due to the advances in technology and the trends it follows. Currently, the development of low-cost devices that are, at the same time, easy-to use and dispose, and produce fast and reliable responses is of eminent significance. Electrochemical biosensors fit perfectly with these requirements, as do paper-based devices. Here we present an enzymatic biosensor using a simple single-use paper-based device in which carbon ink is deposited in a hydrophilic area delimited by wax printing for acting as working electrode. Low-cost gold-plated connector headers are employed as reference and auxiliary electrodes as well as connections to the potentiostat. Glucose oxidase (GOx), horseradish peroxidase (HRP) and potassium ferrocyanide used as mediator of the electron transfer are adsorbed in the ink.